Orphan receptor GPR153 facilitates vascular damage responses by modulating cAMP levels, YAP/TAZ signaling, and NF-κB activation - Jingchen Shao; Jeonghyeon Kwon; Tianpeng Wang; Stefan Günther; Lukas S. Tombor; Timothy Warwick; Zaib Shaheryar; Ralf P. Brandes; Stefanie Dimmeler; Jan Wenzel; Stefan Offermanns; Markus Schwaninger; et al. (Nature Communications)
Abstract Vascular cells express various G-protein-coupled receptors (GPCRs) with yet unknown function, among them orphan receptor GPR153. GPR153 was upregulated in smooth muscle cells (SMCs) in response to injury, and knockdown of GPR153 resulted in reduced proliferation and mildly altered differentiation in human SMCs. Mice with tamoxifen-inducible, SMC-specific GPR153 deficiency were partially protected against ligation-induced neointima formation, and their SMCs were characterized by reduced proliferation and dedifferentiation. Mechanistically, we show that GPR153 negatively regulates cellular cAMP levels, and thus the absence of GPR153 leads to an increase in CREB phosphorylation, reduced YAP/TAZ levels, and diminished NF-κB activation. Interestingly, a similar role of GPR153 was observed in endothelial cells (ECs), where loss of GPR153 resulted in reduced inflammatory gene expression and protected mice with EC-specific GPR153 deficiency in models of neuroinflammation and stroke. Taken together, orphan receptor GPR153 facilitates pro-inflammatory and pro-proliferative gene expression in ECs and SMCs by controlling cellular cAMP levels, thereby contributing to inflammation and vascular remodeling.